2013
DOI: 10.1136/vetreccr.b4763rep
|View full text |Cite
|
Sign up to set email alerts
|

Infectious canine hepatitis in red foxes (Vulpes vulpes) in the United Kingdom

Abstract: The pathological findings are described in three cases of infectious canine hepatitis in free-ranging red foxes (Vulpes vulpes) in England. The foxes died after short periods of clinical illness. Mild jaundice and hepatic congestion were evident grossly. On histopathological examination, intranuclear inclusion bodies were visible in hepatocytes, in association with hepatocyte dissociation and necrosis, as well as in renal glomeruli, renal tubular epithelial cells and vascular endothelial cells. Canine adenovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
(10 reference statements)
0
17
0
Order By: Relevance
“…Another possible source of infection is wild carnivores susceptible to CAdV-1, in Western Europe being mainly foxes and mustelids. In some studies, a CAdV seroprevalence has been indicated in red foxes (Vulpes vulpes) of 19% to 64.4% in the UK (Thompson et al, 2010;Walker et al, 2016a), 3,5% in Germany (Truyen et al, 1998), and 59,6% in Scandinavia (Akerstedt et al, 2010). Unfortunately, the serological examinations cannot distinguish CAdV-1 from CAdV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible source of infection is wild carnivores susceptible to CAdV-1, in Western Europe being mainly foxes and mustelids. In some studies, a CAdV seroprevalence has been indicated in red foxes (Vulpes vulpes) of 19% to 64.4% in the UK (Thompson et al, 2010;Walker et al, 2016a), 3,5% in Germany (Truyen et al, 1998), and 59,6% in Scandinavia (Akerstedt et al, 2010). Unfortunately, the serological examinations cannot distinguish CAdV-1 from CAdV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Occasional reports in domestic dogs have been published suggesting a recrudescence of the disease (Decaro et al 2007a). However, surveys conducted in domestic dogs between 1964-2006 in Brazil (Inkelmann et al 2007) detected 2.1% of ICH cases, while in UK 80 cases of ICH were reported in dogs submitted to one centre in the UK from 1986 to 2007 (Thompson et al 2010), providing evidence of ongoing exposure of susceptible dogs to CAdV-1 and suggesting that the occurrence of ICH has probably been underestimated due to underreporting in the last decades. The importance of considering CAdV-1 as a putative aetiological agent when clinical signs are consistent with ICH (Muller et al 2010), as well as persisting with vaccination against CAdV-1/ICH at a worldwide level is necessary in order to increase the immunity of dog populations and to reduce the risk of CAdV-1 transfer from wildlife reservoirs to susceptible dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Serological positivity to both CAdV types has been detected in additional members of the order Carnivora such as various bears, coyote, jackal, raccoon, wolf, etc. PCR detection and isolation were accomplished from samples of red foxes (Vulpes vulpes) in the UK (Thompson et al, 2010) and in Italy (Balboni et al, 2013). More recently, new AdVs, genetically most closely related to CAdVs, have been discovered and, based on their clustering on the phylogenetic trees, a close common ancestry of CAdV-1, -2 and the AdV of certain vespertilionid bats have been hypothesized (Kohl et al, 2012;Vidovszky et al, 2015).…”
Section: Introductionmentioning
confidence: 99%